LITERASI MEDIA BERITA DAN LITERASI DIGITAL TERHADAP PARTISIPASI POLITIK ONLINE DAN OFFLINE - Lara Sati (MediaKom : Jurnal Ilmiah Komunikasi, 2016)
Abstract: This research is motivated by the condition that the modern mass media technology has drasticallychanged the community. The skills and competence of media literacy and digital literacy are closely related toeach other that is needed to live and work in a diverse community of media-information. Participation in theelectoral process include more than just a voice. Political participation comes from freedom of speech,assembly and association, the ability to take part in the implementation of public affairs, and the opportunity toregister as a candidate, campaigning, to have and to hold office at all levels of government. In this research, thedata collected through experimentation methods quasi the non equivalent control group design. In quasiexperimental pretest / posttest data were collected before and after the intervention (treatment). Comparison ofthe control group and the experimental group at the end of the study showed the effect of the experimentalstimulus. The results of the analysis find that the news media literacy increasing the online and offline politicalparticipation, and the digital literacy increasing the online and offline political participation. Keywords: news media literacy, digital literacy, online and offline political participation